From Head to Toe: Evidence for Selective Brain Activation Reflecting Visual Perception of Whole Individuals - Schmalzl, Laura; Zopf, Regine; Williams, Mark A. (Frontiers in Human Neuroscience, 2012)
Our ability to recognize other people’s faces and bodies is crucial for our social interactions. Previous neuroimaging studies have repeatedly demonstrated the existence of brain areas that selectively respond to visually presented faces and bodies. In daily life, however, we see "whole" people and not just isolated faces and bodies, and the question remains of how information from these two categories of stimuli is integrated at a neural level. Are faces and bodies merely processed independently, or are there neural populations that actually code for whole individuals? In the current study we addressed this question using a functional magnetic resonance imaging adaptation (fMRI-A) paradigm involving the sequential presentation of visual stimuli depicting whole individuals. It is known that adaptation effects for a component of a stimulus only occur in neural populations that are sensitive to that particular component. The design of our experiment allowed us to measure adaptation effects occurring when either just the face, just the body, or both the face and the body of an individual were repeated. Crucially, we found novel evidence for the existence of neural populations in fusiform as well as extrastriate regions that showed selective adaptation for whole individuals, which could not be merely explained by the sum of adaptation for face and body respectively. The functional specificity of these neural populations is likely to support fast and accurate recognition and integration of information conveyed by both faces and bodies. Hence, they can be assumed to play an important role for identity as well as emotion recognition in everyday life.